Corruption Crime: the concept, structure, dynamics - Begalinova, K.K.; Kabanbaeva, G.B. (Journal of actual problems of jurisprudence, 2018)
This article discusses one of the most pressing problems of today. Corruption in government in modern Kazakhstan is one of the most pressing problems without a radical solution that can not be effective development of Kazakhstan’s society. The negative effects of corruption can be put at the center of all the current social conflicts in Kazakhstan. Socio-destructive consequences of corruption manifest in all the spheres of public life. Therefore, the state in which power is highly corrupt, can not be considered neither democratic nor legal, nor social. Corruption in government is a uniquely great social threat, as it directly or indirectly affects the social values, morality, and the foundations of statehood Key words: corruption, public service, crime, officer, public authorities.